EVALUASI TINGKAT GETARAN PADA FAN BLOWER MENGGUNAKAN PEGAS PEREDAM DAN TANPA PEREDAM UNTUK MENGANALISA KARAKTERISTIK GETARAN YANG DIHASILKAN - Tony Siagian (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2026)
This study aims to examine the extent to which the vibration level correlation occurs in a blower under variations in the use of vibration-damping springs compared to the absence of damping springs on the blower shaft, as measured in the vertical, horizontal, and axial directions using an SKF Vibration Analyzer. Based on the comparative analysis of vibration level correlation, a correlation coefficient (rxy) of 0.9793 was obtained for the configuration of six damping springs versus zero damping springs; a coefficient of 0.9800 was obtained for the configuration of four damping springs versus zero damping springs; and a coefficient of 0.9959 was obtained for the configuration of six damping springs versus four damping springs. These findings indicate that the most stable vibration correlation occurred in the configuration comparing six damping springs to four damping springs, which also suggests that the relationship between the increase and decrease in vibration levels was strongest in this configuration compared to the other spring-number configurations. The results further reveal that increasing the number of damping springs does not necessarily produce a significant reduction in vibration compared to the use of fewer damping springs. Consequently, further evaluation is required regarding the blower installation method as well as the selection of a more appropriate type of vibration damper.